2022
DOI: 10.3390/ijerph19127157
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Built Environment on Risk of Women’s Lung Cancer: A Case Study of China

Abstract: Built environment factors such as air pollution are associated with the risk of respiratory disease, but few studies have carried out profound investigation. We aimed to evaluate the association between the built environment and Chinese women’s lung cancer incidence data from the China Cancer Registry Annual Report 2017, which covered 345,711,600 people and 449 qualified cancer registries in mainland China. The air quality indicator (PM2.5) and other built environment data are obtained from the China Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The existing studies have demonstrated that genes (family history) and living habits (smoking, second-hand smoke, and kitchen smoke) contribute to the risk of lung cancer [ 25 , 26 ]. Tobacco is an important risk factor for tumours and the prevalence of smoking is generally higher in Chinese men than in women [ 27 ], which may explain the higher incidence of lung cancer in men than in women. And the study found that 61% of women who died of lung cancer were nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…The existing studies have demonstrated that genes (family history) and living habits (smoking, second-hand smoke, and kitchen smoke) contribute to the risk of lung cancer [ 25 , 26 ]. Tobacco is an important risk factor for tumours and the prevalence of smoking is generally higher in Chinese men than in women [ 27 ], which may explain the higher incidence of lung cancer in men than in women. And the study found that 61% of women who died of lung cancer were nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Their exhaustive systematic review illuminated the profound influence of transportation, land use, and housing in shaping cancer incidences, thereby bridging the gap between the built environment and cancer outcomes. Xie et al (2022) ventured into the Chinese landscape, investigating the correlation between the built environment, characterized by land-use intensity and green coverage ratio, and the prevalence of Women's Lung Cancer. Their findings revealed pronounced regional disparities, with Heilongjiang, Liaoning, and Inner Mongolia grappling with elevated incidence rates, while Tibet, Xinjiang, and Hainan exhibited comparably lower rates.…”
Section: Literature Reviewmentioning
confidence: 99%